Scientific challenges faced by Mn‐based layered oxide cathodes with anionic redox for sodium‐ion batteries - Chao Zheng; Shengnan He; Jiantuo Gan; Zhijun Wu; Liaona She; Yong Gao; YaXiong Yang; Jiatao Lou; Zhijin Ju; Hongge Pan (Carbon Energy)
Abstract In the realm of sodium‐ion batteries (SIBs), Mn‐based layered oxide cathodes have garnered considerable attention owing to their anionic redox reactions (ARRs). Compared to other types of popular sodium‐ion cathodes, Mn‐based layered oxide cathodes with ARRs exhibit outstanding specific capacity and energy density, making them promising for SIB applications. However, these cathodes still face some scientific challenges that need to be addressed. This review systematically summarizes the composition, structure, oxygen‐redox mechanism, and performance of various types of Mn‐based cathodes with ARRs, as well as the main scientific challenges they face, including sluggish ion diffusion, cationic migration, O2 release, and element dissolution. Currently, to resolve these challenges, efforts mainly focus on six aspects: synthesis methods, structural design, doped modification, electrolyte design, and surface engineering. Finally, this review provides new insights for future direction, encompassing both fundamental research, such as novel cathode types, interface optimization, and interdisciplinary research, and considerations from an industrialization perspective, including scalability, stability, and safety.